2014
DOI: 10.1007/s11999-013-3425-5
|View full text |Cite
|
Sign up to set email alerts
|

Can Internet Information on Vertebroplasty be a Reliable Means of Patient Self-education?

Abstract: Background Studies of the quality and accuracy of health and medical information available on the Internet have shown that many sources provide inadequate information. However, to our knowledge, there are no published studies analyzing the quality of information available online regarding vertebroplasty. Because this has been a highvolume procedure with highly debated efficacy, it is critical that patients receive complete, accurate, and well-balanced information before deciding a treatment course. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 33 publications
(54 reference statements)
1
19
0
5
Order By: Relevance
“…[47, 48, 50] One article used author-generated criteria to grade the websites and another used the Ensuring Quality Information for Patients (EQIP) tool. [46, 49]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47, 48, 50] One article used author-generated criteria to grade the websites and another used the Ensuring Quality Information for Patients (EQIP) tool. [46, 49]…”
Section: Resultsmentioning
confidence: 99%
“…[46-49] Mean DISCERN criteria scores ranged from 40 – 60 (out of 80) and only 4-30% of the websites bore the HONcode seal. Websites with HONcode certification had significantly higher mean DISCERN scores (58.0 v 39.8).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not easy to find a reliable answer using Internet search engines. Numerous studies of the accuracy of medical information obtained by Internet search engines have shown that a considerable portion of such information is misleading . On the other hand, even if online materials are accurate and reliable, they are only useful when one has a clear understanding of their meaning.…”
mentioning
confidence: 99%
“…Numerous studies of the accuracy of medical information obtained by Internet search engines have shown that a considerable portion of such information is misleading. [4][5][6][7][8][9] On the other hand, even if online materials are accurate and reliable, they are only useful when one has a clear understanding of their meaning. Although there are many review articles and guidelines that offer scientifically proven information on the Internet, they are written for professionals and thus contain many technical terms that are not easily understood by the layperson.…”
mentioning
confidence: 99%
“…The concerns for self-education are real, with one study showing that of 105 websites dedicated to vertebroplasty education, 19% were classified as poor quality with 57% as unacceptable (Sullivan, Anderson, Ahn, & Ahn, 2014 Finally, patients and doctors commented that finding a legitimate source for self-education was difficult and this is partly due the readability of most authoritative web pages, with current literature suggesting that of 251 web pages with information on 12 common health conditions identified across sectors, the readability of Australian sites exceeds the average Australian levels of reading (Cheng & Dunn, 2015).…”
Section: Self-educationmentioning
confidence: 99%